ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERHADAP KEPUTUSAN PENGGUNAAN LINK AJA SYARIAH - Ambiko Maranendha Panerang; Nia Utami (LPPM - STIE SAKTI ALAM KERINCI, 2023)
Technology is developing rapidly due to an increasingly sophisticated era, demanding that everyone must be prepared for the emergence of new technology. As fintech develops from time to time, a payment system is needed that facilitates transactions at any time and from any location. LinkAja presents the LinkAja Syariah Service, the first and only sharia electronic money in Indonesia that can facilitate various transactions. This research is a quantitative study. Googleform-facilitated questionnaire distribution. The decision making process is just some of the indicators included in the questionnaire to estimate the research variables. A total of 101 respondents were selected as the population through the non-probability sampling method. In accordance with Article 1 number 7 of Bank Indonesia Regulation Number 18/40/PBI/2016 of 2016, which describes the Implementation of Payment Transaction Processing (